2021
DOI: 10.1111/jpm.12758
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of patients’ and staff’s perspectives on the causes of violence and aggression in psychiatric inpatient settings: An integrative review

Abstract: What is known on the subject?• Aggression and violence are persistent problems in psychiatric inpatient units.• Violence preventive factors have been identified from both staff's and patients' perspectives.• Violent and aggressive inpatient incidents have not been adequately explained in research and reviews to date. What this paper adds to existing knowledge?• This review is novel in that it provides a comparison of patients' and staff's perspectives and identified that these differ and were influenced by fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 49 publications
0
21
0
1
Order By: Relevance
“…However, conflict and violence in mental health wards is a complex issue that affects both staff and patients (Bowers 2014 ; Fletcher et al . 2021 ; Kumar et al . 2001 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, conflict and violence in mental health wards is a complex issue that affects both staff and patients (Bowers 2014 ; Fletcher et al . 2021 ; Kumar et al . 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, conflict and violence in mental health wards is a complex issue that affects both staff and patients (Bowers 2014;Fletcher et al 2021;Kumar et al 2001). Research and audits conducted in inpatient services in England revealed patients often experience verbal abuse, fighting, bullying, theft, racism, and sexual assault (Care Quality Commission 2018;Jones et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The findings of the study reflect the results of a document analysis from Hong Kong, which revealed that the local hospital guidelines may not support international standards regarding the reduced use of restrictive interventions [ 37 ]. Therefore, understanding how the inpatient culture plays a role in shaping a dynamic between patients and staff and developing communication skills that acknowledge this may help reduce violence and aggression in inpatient settings [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Current explanation of reasons for aggression is a combination of factors embodied in patients, staff and the ward environment [ 7 ]. On the other hand, aggressive inpatient incidents have not been adequately explained in research [ 10 ]. When management of aggression is a focus of treatment, opinions for aggression should be shared from different points of view, including those of clinicians, patients, and families [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alongside concerns regarding the validity of risk assessment in predicting suicide, there is also a strong argument that such practices implemented by health services to manage risk, such as formal observations, can be countertherapeutic and carry many costs to those with lived experience (Manuel et al 2018). A key determinant in the process of risk assessment is the person's psychiatric diagnosis; however, those with lived experience have suggested that increase in the risk of harm is linked to the clinical culture (Fletcher et al 2021).…”
Section: Psychiatric Discoursementioning
confidence: 99%